Synthesis, Characterization and Adsorption of Metal Ions on New Silica-Gel Organofunctionalized Compound - KHOSRAVAN, M.; FATEMI, S.J.; SALJOOGHI, A.S. (Asian Journal of Chemistry, 2010)
Silica gel chemically modified with organic groups is widely used as an adsorbent for metal ions. In this investigation, silica gel was chemically modified with 3-chloropropyltrimethoxysilane and reacted with 2-aminothiophenol in order to yield an aromatic group immobilized on the silica gel surface and produced a compound for adsorbing Fe3+, Co2+, Ni2+, Cu2+, Zn2+, Cd2+, Tl+ and Tl3+ ions, which prepared in buffer solution at physiological pH. The characterization of new compound and its capability towards extraction of the above metal ions were studied and evaluated by a batch method. This compound showed high performance toward Fe3+ extraction, where its adsorption determined to be 98.1%. The order of increasing the metal ions uptake process satisfactorily coincides with increasing the hardness of these metal ions.